Keresahan akibat kelangkaan dan kenaikan harga pupuk bagi para petani di Indonesia - Aditya, Rengga (Maliki Interdisciplinary Journal, 2024)
The rise in chemical fertilizer prices and scarcity in recent years has significantly impacted the welfare of farmers in Indonesia. Small-scale farmers, especially those relying on fertilizers to enhance crop productivity, face difficulties due to the high prices of fertilizers, which can reach double their previous costs. Although there are fertilizer subsidy programs, their implementation is often uneven, hindering farmers' access. In this context, concrete measures from the government and related institutions are needed to stabilize prices and improve fertilizer distribution efficiency. Additionally, promoting the use of organic fertilizers as an alternative is crucial for supporting food security in the future.